O Programa Creche Escola e sua(s) concepção(ões) de Educação Infantil: entre o Estado e o Município - Perea, Nayane Moreno (Universidade Federal de São Carlos, 2019)
The state program Creche Escola intends to expand early childhood education services primarily in areas with greater social vulnerability and shortage of vacancies, through an agreement signed between the State of São Paulo and the associated São Paulo municipality under the constitutional system of collaboration. While the purpose of this program is the construction and equipping of early childhood education units for municipalities with state resources, the state starts to act in a modality that is not mandatory, which instigated us to investigate the conception(s) of early childhood education involved in the program, taking into account the state perspective and the municipal perspective, based on the case study of Araraquara/SP (2011-2018). For this purpose, we conducted a qualitative data study, a case study, whose methodological path involved the execution of ethical procedures, bibliographic, documentary and empirical characters, manifested through a semi-structured interview. The state proposal is significant when it is proposed to finance early childhood education units, given the high demand for vacancies and the municipal recourse limitations to offer them properly. However, the Creche Escola, anchored in the precepts of the New Public Management, denotes a private view of care, notably by targeting especially the most vulnerable and by idealizing a practical architectural project at minimum cost. Not by chance, as seen, that such architectural design does not conceive the pedagogical specificities of the young child, since, taking the economic logic into consideration, it represents the impoverishment of the school infrastructure, which is reduced to a space of shelter and care for toddlers and a space that prepares primary education for the older children, leaving aside the fun and the playfulness and giving their underprivileged children a poor education. However, in practice, despite the fact that the municipality has to follow the building project according to the definitions and conceptions of the state, Araraquara, for its solid history in early childhood education, with its own architectural design and a standard child care, tries to print in spaces of the Creche Escola unit a conception of similar education, which does not separate education and caring, relating both to fun and playfulness. As we have seen, within the Creche Escola Program, the pedagogical and administrative work of the new units are responsibility of the municipality, according to its network and its conceptions, so that there is a tendency for the Program to sustain various conceptions of early childhood education under the same architectural design, depending on the associated municipality.
The Creche Escola Program and its conception(s) of early childhood education: between the State and the Municipality
Keywords: Programa Creche Escola; Política Educacional Paulista; Educação Infantil; Creche Escola Program; Educational Politics of the State of São Paulo; Early Childhood Education; CIENCIAS HUMANAS::EDUCACAO